CLINICAL AND LABORATORY CORRELATION OF BILIRUBIN INDUCED NEUROLOGICAL DYSFUNCTION IN NEONATAL CHILDRENS (International journal of medical sciences, 2026)
According to the WHO, complications of pathological jaundice in children are a leading cause of disability and mortality and continue despite universal newborn screening. Further research into the neurological and clinical aspects of bilirubin encephalopathy and jaundice is needed. This article reviews various clinical and pathological conditions associated with jaundice and bilirubin encephalopathy, as well as diagnostic tests used in patients with these conditions. The authors aim to convey to pediatric neurologists and neuropathologists the importance of early diagnosis and prevention of the disease. Acute bilirubin encephalopathy (ABE) is a cause of morbidity and mortality worldwide, particularly among infants and young children.